Structure features and paramagnetic centres in oxide nanopowders - Shevchuk, V.N.; Popovych, D.I.; Usatenko, Yu.N.; Demchenko, P.Yu.; Serkiz, R.Ya. (Functional Materials, 2009)
Nanopowders ZnO, SiO₂, SiO₂/10 % V₂O₅ obtained by sol-gel technology were investigated by electron paramagnetic resonance (EPR) method at temperature of liquid nitrogen. The structures of the samples are analyzed by X-ray diffraction method. Surface morphology and chemical elementwise composition of powders were studied using scanning electron microscopy. For the nanocomposite SiO₂/10 % V₂O₅ structure of EPR spectrum is described as a result of unpaired electron and isotope nucleus ⁵¹V interaction. The prevailed EPR signal in ZnO is hypothetically associated with single-charge vacancy in oxygen sub-lattice.